(untitled) (Моделювання, керування та інформаційні технології, 2020)
The paper outlines that the practice employment is interested in the highly skilled staff delivered by information technology education. Practice acts as the important criterion of quality check of preparation of technologies entrepreneur, checks the validity, value and an efficiency of scientific research on the basis of which formation is educated. Creation of conditions to protect interests of young specialists and to promote their employment on a labor market is of great importance for economic, demographic, social or political advancement in the region and on all country, just as for improvement of social and economic environment.